Screening of Infectious Diseases and Hb Levels at Blood Donor Unit Indonesian Red Cross in Jayapura City Papua - Herlando Sinaga; Ester Rampa; Rini Susanti; Rima Anglia (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Voluntary blood donors are people who voluntarily donate their blood to other people and not to certain patients. Before blood is given to the recipient, a blood filter test or screening test is carried out. A screening test is a process of screening or separating blood that can be transfused and not infected with an infectious disease. Research has been conducted with the title Infectious Disease Screening Results and Hemoglobin (Hb) Levels in Voluntary Donors at the Indonesian Red Cross Blood Transfusion Unit, Jayapura City. This research was conducted for 1 month, from 13 May to 15 June 2019. The population used in this study were all voluntary donors who came to donate blood. The number of samples in this study was 45 samples. Methods for examining infectious diseases, in this case testing for HIV, HBsAg, and hemoglobin levels used were the ELISA method and Bj: 1.053 copper sulfate. 2 people (4.4%) were positive and 43 people (95.6%) negative, HBsAg test found 7 people (15.6%) positive and 38 people (84.4%) negative and Hemoglobin obtained results as many as 45 people (100%) normal.